Development of Balinese Customary Law in the Perspective of Local Wisdom “Tri Hita Karana’’ - Nyoman Gede Antaguna; I Nyoman Putu Budiartha (Fakultas Hukum, Universitas Warmadewa, 2023)
This research article explores the development of Balinese Customary Law within the context of the profound local wisdom known as